2012
DOI: 10.1021/ja211115q
|View full text |Cite
|
Sign up to set email alerts
|

Protein Crowding Affects Hydration Structure and Dynamics

Abstract: The effect of protein crowding on the structure and dynamics of water was examined from explicit solvent molecular dynamics simulations of a series of protein G and protein G/villin systems at different protein concentrations. Hydration structure was analyzed in terms of radial distribution functions, three-dimensional hydration sites, and preservation of tetrahedral coordination. Analysis of hydration dynamics focused on self-diffusion rates and dielectric constants as a function of crowding. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
253
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(274 citation statements)
references
References 46 publications
20
253
0
1
Order By: Relevance
“…Molecular dynamic simulations showed that the backbone fluctuations of CI2 increase in lysozyme, which correlates with its destabilizing effect . Harada et al (2012) used molecular dynamics to show that protein crowders reduce the dielectric constant of the solution. This decrease would diminish the hydrophobic effect while enhancing hydrogen bond strength.…”
Section: Crowding and Assemblymentioning
confidence: 99%
“…Molecular dynamic simulations showed that the backbone fluctuations of CI2 increase in lysozyme, which correlates with its destabilizing effect . Harada et al (2012) used molecular dynamics to show that protein crowders reduce the dielectric constant of the solution. This decrease would diminish the hydrophobic effect while enhancing hydrogen bond strength.…”
Section: Crowding and Assemblymentioning
confidence: 99%
“…In a recent KITA investigation of peptide substrate binding to a human metalloproteinase, no conclusion was reached as to whether water motions preceded or followed enzyme motions [23]. In contrast, numerous studies of protein folding and of proteins and nucleic acids passing through their glass transition temperatures (the temperature below which the hydrated macromolecule shows highly restricted movement and little or no biological activity) have generally indicated that more-rapid changes in local water structure precede the slower, major conformational changes of the macromolecules [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Historical Background: Advances In Measurement Of Biologicalmentioning
confidence: 99%
“…Could water CDs provide a physical basis for overcoming both the kT paradox and the intracellular crowding problem [28,29,31,[164][165][166][167][168][169][170][171][172]? The term kT requirement, where k is the Boltzmann constant and T is temperature (deg K), relates generally to the temperature dependence of chemical reaction rates, and the need to impart enough energy to biological molecules in cells to achieve such reactions at physiological temperatures, without resorting to thermal diffusion (i.e., heating up the reactants).…”
Section: Overcoming the Kt Or "Thermal Diffusion" Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit popular, Eq. 2 and most treatments of hydrodynamic interactions do not account for the perturbation of the solvent caused by crowding agents (Harada et al 2012;Mukherjee et al 2015;Wang et al 2017b) or by protein-specific effects (Huang et al 2016). …”
Section: System Representation Force Field Parameterization and Dynmentioning
confidence: 99%